Resilience and Compassion Fatigue Among Registered Nurses in Ghana - OSEI, SIMON AKWASI; ANTWI, FISKVIK BOAHEMAA; Peprah, Williams Kwasi (11th International Scholars Conference, 2019)
In the healthcare sector, nurses provide health care services to different clients which can result in compassion fatigue. The resilience of nurses helps to provide control of compassion fatigue. The purpose of this study is to examine if there is a relationship between resilience and compassion fatigue and also find a significant difference in resilience and compassion fatigue in terms of sex, age, and clinical experience. Correlational research design was utilized where 249 registered nurses were conveniently sampled from Ghana. The study utilized a Resilience questionnaire Scale developed by Wagnild and Young (2010) and Professional quality of life (ProQOL) scale developed by Stamm (2010) was adapted and modified for compassion fatigue. The statistical treatments used were and Pearson Correlation, T-Test and ANOVA to address the research questions. The study showed that there was a high positive significant relationship between resilience and compassion fatigue. There was a significant difference in age and sex on compassion fatigue however, no significant on clinical experience. Sex and clinical experience showed a significant difference in resilience but no significant difference when age was considered. The results of the study suggest that registered nurses in Ghana experience high compassion fatigue. In preventing the compassion fatigue of the nurse's measures should be instituted to increase the resilience level of the nurses. Healthcare administrators should put in measures to reduce the compassion fatigue of the nurses. Further researchers should explore other variables in relation to the resilience to help reduce the compassion fatigue of nurses